2022
DOI: 10.5267/j.ijdns.2022.5.004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding artificial intelligence experience: A customer perspective

Abstract: The engagement between customers and brands is being transformed by artificial intelligence (AI). However, there has been little study into AI-powered customer experiences; hence, this research aims to examine how the incorporation of AI in purchasing might result in a better AI-powered customer experience. This research will develop a conceptual model based on the service quality model and trust-commitment theory. Further to this, an online questionnaire was distributed to individuals who had utilised an AI-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Even though social networks have been recognized as significant for surviving the current global pandemic (e.g., Fabeil et al, 2020;Trawnih et al, 2021), Jordanian SMEs still lack in successfully adopting the process (Trawnih et al, 2022). Al Tawara and Gide (2017) have found that a key reason for the low productivity of SMEs in Jordan is the lack of adoption intentions toward social media.…”
Section: Social Commerce In Smesmentioning
confidence: 99%
“…Even though social networks have been recognized as significant for surviving the current global pandemic (e.g., Fabeil et al, 2020;Trawnih et al, 2021), Jordanian SMEs still lack in successfully adopting the process (Trawnih et al, 2022). Al Tawara and Gide (2017) have found that a key reason for the low productivity of SMEs in Jordan is the lack of adoption intentions toward social media.…”
Section: Social Commerce In Smesmentioning
confidence: 99%
“…Generative artificial AI offers substantial assistance to enterprises, particularly in virtual try-on, virtual shopping assistance, and product customization [43]. AI technologies significantly improve customer engagement by providing deeper insights into consumer behavior, allowing firms to design more tailored and engaging marketing efforts [44]. AI-powered solutions, including recommendation systems and chatbots, enable real-time consumer interactions while providing individualized suggestions and assistance.…”
Section: Theoretical/conceptual Frameworkmentioning
confidence: 99%
“…Companies must find ways to simplify these explanations while ensuring the accuracy of the information provided. Additionally, accountability is essential when AI systems make errors or produce biased results to ensure that there are clear responsibilities and mechanisms in place to address and rectify these issues effectively [44]. Organizations and individuals should be held responsible for the outcomes of AI systems to ensure ethical practices, foster trust, and promote the development of reliable and unbiased AI technologies.…”
Section: Ethical Considerations and Regulatory Compliancementioning
confidence: 99%
“…The main objective of this research is to investigate and understand the intricate relationship between AI services and customer satisfaction [8]. AI technology offers significant opportunities for enhancing customer interactions and providing more personalized services.…”
Section: Introductionmentioning
confidence: 99%